The lock-in effect of marriage: Work incentives after saying, "Yes, I do." - Michael Christl; Silvia De Poli; Viginta Ivaškaitė-Tamošiūnė (Global Labor Organization (GLO), 2022)
In this paper, we use EUROMOD, the tax-benefit microsimulation model of the European Union, to investigate the impact of marriage-related tax-benefit instruments on the labour supply of married couples. For each married partner, we estimate their individual marginal effective tax rate and net replacement rate before and after marriage. We show that the marriage bonus, which is economically significant in eight European countries, decreases the work incentives for women and, particularly, on the intensive margin. In contrast, the incentives on the intensive margin increase for men once they are married, pointing to the marriage-biased and gender-biased taxbenefit structures in the analysed countries. Our results suggest that marriage bonuses contribute to a lock-in effect, where second earners, typically women, are incentivised to work less, with negative economic consequences.
Keywords: H31; J12; J22; 330; marriage; cohabitation; marriage bonus; work incentives; gender; tax-benefit system; labour supply; Europe